Zaire's Hyperinflation, 1990-96 - Beaugrand, Philippe (IMF Working Papers; Working Paper ;, 1997)
This paper reviews Zaire's experience with hyperinflation during 1990-96 and develops an illustrative model based on a money demand function that includes government revenue as a determinant. Government revenue is itself subject to the 'Tanzi effect,' in which inflation tends to lower revenue collections. The model is estimated over the 1990-96 period, and simulations are also presented. The paper concludes with a number of observations and policy recommendations for stopping hyperinflation in Zaire.